Effectiveness of Purple Sweet Potato (Ipomoea batatas L.) Pressed Water as a Natural Coloring Agent for Examination of Feces Confirmed Helminthiasis - Faatiha, Arsyal Wanda; Aisyah, Riandini; Dewi, Listiana Masyita; Rosyidah, Devi Usdiana (Universitas Muhammadiyah Surakarta, 2024)
Background: Helminthiasis is a parasitic disease caused by worms, with high prevalence in Indonesia ranging from 2.5% to 62%, depending on the region. Soil transmitted helminths are the most common causative of helminthiasis. The Gold Standard diagnose helminthiasis is microscopic examination using eosin. However, Eosin has the disadvantage that the waste from its use is not environmentally friendly and carcinogenic, prompting the search for natural dye alternatives. Purple sweet potato (Ipomoea batatas L.), rich in anthocyanins, was selected as a potential substitute because it contains higher anthocyanin levels compared to other plants. Aim: This study aimed to evaluate effectiveness of purple sweet potato pressed water as a substitute for eosin and to assess the differences between pure pressed water and with added citric acid in staining feces confirmed with helminthiasis. Methods: The study utilized a true experimental design with posttest-only control group approach. Purple sweet potato pressed water was tested at varying concentrations 5%, 10%, 15%, 20% and as well as at the same concentrations with the addition of citric acid. The population consisted of helminthiasis confirmed stool samples preserved in formalin. Staining effectiveness was assessed using Likert scale, and data were analyzed using Shapiro-Wilk, Levene, and Kruskal-Wallis tests. Results: Purple sweet potato pressed water without citric acid demonstrated good staining quality, result of Kruskal-Wallis p-values for coloring effectiveness (p=0.195), visualization of parasite structure (p=0.566), coloring quality (p=0.062). Conclusion: Purple sweet potato pressed water can be used as an alternative dye in helminthiasis examination. The addition of citric acid in the preparation can increase the stability of the formulation.